Addition of intestinal alkaline phosphatase in diets and its effects on growth performance and intestinal health of weaned piglets challenged with escherichia coli k88+ - Genova, Jansller Luiz (2020)
In this study, our aim was to assess the additional effect of intestinal alkaline phosphatase (IAP) in diets on growth performance, diarrhea occurrence (DO), blood metabolites, intestinal histology, relative organ weights, bacterial population counts, pH of digestive tract content, hepatic glycogen reserve (HGR), histopathological description and proinflammatory markers of piglets challenged with enterotoxigenic Escherichia coli (ETEC) K88+. A total of 64 crossbred piglets, entire male, weaned at 25-days-old with an average initial body weight of 7.168 ± 0.287 kg were allocated to a randomized complete block design consisting of four treatments repeated twice in the two blocks: control diet (negative control), control diet + antimicrobial growth promoter (AGP, 150 g of tiamulin/ton of diet), control diet + 15 mg IAP/kg of diet and control diet + 30 mg IAP/kg of diet, four replications per block with two piglets per experimental unit. All piglets were orally challenged with 6 mL of a solution containing ETEC K88+ (106 CFU/mL). Prior to the beginning of the experimental period, was determined the best microencapsulation process of IAP in a model involving adhesion and phagocytic activity of equine bronchoalveolar macrophage. In Exp. I, the variables analyzed were growth performance, DO, blood metabolites (urea, glucose and alkaline phosphatase), intestinal morphometry, relative organ weight and in vitro simulation of microencapsulated IAP on pH modulation capacity and its dilution in acidic and basic solution. At 19 experimentation days, six animals per treatment were slaughtered for data collection and biological samples. Exp. II involved the evaluation of the effect of IAP on intestinal health by bacterial populations counts in the intestinal content and adhered to mesenteric lymph node, digestive organ content pH, HGR, proinflammatory markers in the liver and intestinal epithelium and histopathological description of the intestinal epithelium. In pre-starter I phase, piglets that received 30 mg IAP added in the diet or control diet showed better feed conversion rate (P = 0.075) compared to those fed 15 mg IAP. Piglets that consumed 30 mg IAP or control diet showed greater (P = 0.004) average daily body weight gain (ADBWG) in the pre-starter II phase. Piglets fed 15 mg IAP had lower average daily feed intake (ADFI) (P = 0.033) compared to piglets with diets containing AGP. At the total period, there was a difference between treatment, in which the piglets fed 15 mg IAP showed a reduction in ADBWG (P = 0.040) and ADFI (P = 0.092). For the pre-starter II phase, there was a difference (P = 0.044) of treatment, in which the piglets that consumed the diet containing 30 mg IAP showed a 24% improvement in DO compared to the treatment with 15 mg IAP. We observed the main effect (P = 0.009), with the addition of 30 mg IAP in the post-challenge phase in decreasing piglet DO (5.56%) when compared to those receiving AGP (16.67%). For the total period, piglets that consumed 15 mg IAP showed greater (P = 0.007) DO when compared to those receiving 30 mg IAP. No differences between treatments were obtained in any of the pre- and post-challenge plasma concentration indicators. The spleen relative weight of piglet increased (P = 0.043) in response to 30 mg IAP treatment. The Enterobacteriaceae counts in the cecum content were lower (P = 0.002) in piglets that receiving 30 mg IAP compared with those for AGP treatment. Piglets fed 30 mg IAP presented lower (P = 0.007) Enterobacteriaceae count in the colon when compared to the other treatments. For the Enterobacteriaceae count adhered to the mesenteric lymph nodes (MLN), there was an increase (P = 0.006) in piglets fed diets with AGP. Piglets fed the control diet or AGP showed greater (P = 0.000) lactic acid bacteria (LAB) count in the cecum content. There was a treatment effect (P = 0.013) on LAB count in MLN, in which piglets fed with AGP or that received 30 mg IAP had a greater count when compared to those with 15 mg IAP. The experimental treatments did not influence (P > 0.05) the pH of the digestive tract contents, intestinal morphology, TNF-α, COX-2 activity, TLR4 and proliferating cell nuclear antigen in the jejunum and liver, nor on HGR. Piglets that received 30 mg IAP showed a slight reduction on TNF-α in jejunum (4.17 times) and liver (1.9 times) when compared to piglets in the control group or with AGP, respectively. Based on the present results, the addition of 30 mg IAP in diets improves the growth performance and attenuates the DO in piglets in the post-weaning period. In addition, the results suggest that the addition of 30 mg IAP provides an ability to mitigate intestinal injuries and maintain the homeostasis of the intestinal physiology of piglets.